The C.L.I.M.B. Commonwealth Large Indoor Mix-Activity Building - Lapira, Anna Dominique M.; Joson, Gerard Thomas F. (Quezon City College of Architecture, University of the Philippines Diliman, 2016)
The purpose of this thesis is to create a facility that will consolidate 'thrill' activities in an indoor setting, within a city. Studies show that the trend for recreation-a human need- is heading towards adventure tourism, which involves activities that can be considered 'thrilling' or even 'extreme'. Some examples of this are: indoor rock climbing, bouldering, scuba pools, bungee jumping, indoor sky diving, and so on. Another significance of the study is its possible effects on the young's psyche, veering them away from destructive behaviors where they get their adrenaline rush, including excessive addiction to video games. It may also help reduce engagement in other sensual-seeking activities like alcoholism, gambling, and even drug-use. Another trend is health-consciousness, even for the younger generations, as well as the increasing reliability of technology. The primary purpose of the design, then, shall not be limited to convenience (primarily due to its consolidated nature) and accessibility (due to its location), but also the creation of an environment people can relax, feel safe, and become healthy while enjoying the exercise. There shall be the creation of experience by using tools and concepts for novelty, diversity, and flow. The building is to be the first of its kind, but it is also novel in that its approach to certain activities will veer away from the usual. It is diverse in the sense that it contains a variety of activity, but also due to its organic form where no two views would be the same. And finally, its flow will also be a source of experience: space to space, activity to activity.
includes appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Sports facilities -- Designs and plans; Interior architecture